2011
DOI: 10.1007/s00167-011-1840-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of isolated chondral and osteochondral defects in the knee by autologous matrix-induced chondrogenesis (AMIC)

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 39 publications
8
124
0
2
Order By: Relevance
“…First in vitro and animal studies showed an enhanced defect filling and higher quality of the repair tissue when a collagen I/III matrix was used and so the authors concluded that repair tissue formation is encouraged when a collagen I/III matrix is used [4][5][6] . Regarding the AMIC technique in the knee joint several studies could show that this method is an effective and safe method of treating fullthickness chondral defects 8,9,[11][12][13] . In the treatment of the ankle joint with the AMIC technique good early and mid-term results are reported; however, the literature today is limited to case series and reports 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First in vitro and animal studies showed an enhanced defect filling and higher quality of the repair tissue when a collagen I/III matrix was used and so the authors concluded that repair tissue formation is encouraged when a collagen I/III matrix is used [4][5][6] . Regarding the AMIC technique in the knee joint several studies could show that this method is an effective and safe method of treating fullthickness chondral defects 8,9,[11][12][13] . In the treatment of the ankle joint with the AMIC technique good early and mid-term results are reported; however, the literature today is limited to case series and reports 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Kusano et al presented clinical and radiographic results in a retrospective study with a mean followup of 29 months of patients treated with AMIC for full-thickness cartilage defects of the knee 13 . They found significant improvements in the IKDC, Lysholm, Tegner and VAS pain score.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In a perspective study, Gille 67 In another study, the same authors found a significant decrease of pain in the VAS (visual analog scale) at 1 and 2 years postoperatively. 68 Kusano et al 69 also detected significant improvements in functional scores and VAS after 29 months, but magnetic resonance imaging (MRI) findings showed generally incomplete or inhomogeneous tissue filling. Comparing AMIC with the original microfracturing technique, Anders et al 70 found no significant differences in the IKDC or Cincinnati score at 1 or 2 year follow-up.…”
Section: Developments In Bone Marrow Stimulating Techniquesmentioning
confidence: 99%
“…The midterm results of this technique nevertheless show that this goal likely will not be achieved in most cases. 4 The aforementioned findings might be at least partially due to a limited number of bone marrow stem cells migrating into the surgically prepared cartilage defect after multiple perforations of the subchondral lamina. The limited bone marrow volume of the patella might aggravate this restriction.…”
mentioning
confidence: 99%
“…Furthermore, the violation of the subchondral bone creates bridging between the bone marrow and joint space, resulting in oxygenation of the defect area, which might be disadvantageous for the generation of the repair tissue. 4 Autologous chondrocyte implantation (ACI) 5 has proved to partially avoid the degeneration of repair tissue and change in phenotype (from cartilage-like tissue toward bone) over time and to produce, in many cases, regenerate tissue quite similar to hyaline joint cartilage histologically with superior mechanical properties. 3 The flaws of this technique are the expense and the need for a 2-stage procedure.…”
mentioning
confidence: 99%